If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9x+30=-5(x+2)
We move all terms to the left:
-9x+30-(-5(x+2))=0
We calculate terms in parentheses: -(-5(x+2)), so:We get rid of parentheses
-5(x+2)
We multiply parentheses
-5x-10
Back to the equation:
-(-5x-10)
-9x+5x+10+30=0
We add all the numbers together, and all the variables
-4x+40=0
We move all terms containing x to the left, all other terms to the right
-4x=-40
x=-40/-4
x=+10
| (8x+9)=(11x+12) | | 2(6x-3)=7(7x-1.2) | | 115+(x+27)=180 | | (4v-3)(v-5=) | | –8s+7=–7s | | 26=6k | | 7(x+5)=24 | | |5m+9|=-31 | | -4r+8+5=-15-3r | | 5w+8.6=-3.4 | | 8(x+5.75)=16(3x+1.50) | | 3/5(x-19)=5 | | 9-2(x+7)=21 | | 22+54x=+60x | | 120=6r | | 5y+6=4y+12 | | 16.95+(.5n)=22.95+(.2n) | | 24m-12=-84 | | 70=3g | | u-2.89=9.3 | | 90=6x-2+20 | | 24=12a-6 | | (5x+10)=(7x+6) | | 4=n+15/9 | | -7+3x=-1x+17 | | y=1/4–2 | | 9(x-2)=830 | | -(15x+3)=-3x-9 | | 19x=1,995 | | y2–45y=0 | | 76+67+5x+2=180 | | 11=-2x+10 |